Changes of drive to recovery ratio during 2000m ergometer rowing among Junior National Rowers - Muhammad Aiman, Umar (Kementerian Pendidikan Tinggi (KPT), Malaysia, 2019)
Link to publisher's homepage at http://www.mohejournal.com/index.php/mohe